Is There a Distress Risk Anomaly? Corporate Bond Spread as a Proxy for Default Risk - Anginer, Deniz (2012)
Although financial theory suggests a positive relationship between default risk and equity returns, recent empirical papers find anomalously low returns for stocks with high probabilities of default. The authors show that returns to distressed stocks previously documented are really an amalgamation of anomalies associated with three stock characteristics -- leverage, volatility and profitability. In this paper they use a market based measure -- corporate credit spreads -- to proxy for default risk. Unlike previously used measures that proxy for a firm's real-world probability of default, credit spreads proxy for a risk-adjusted (or a risk-neutral) probability of default and thereby explicitly account for the systematic component of distress risk. The authors show that credit spreads predict corporate defaults better than previously used measures, such as, bond ratings, accounting variables and structural model parameters. They do not find default risk to be significantly priced in the cross-section of equity returns. There is also no evidence of firms with high default risk delivering anomalously low returns.